The prevalence and risk factors of postpartum depression among women during the early postpartum period: a retrospective secondary data analysis - Jung-Mei Tsai; Li-Yun Tsai; Shiow-Luan Tsay; Yi-Heng Chen (Elsevier, 2023)
Objective: Postpartum depression (PPD) is common and detrimental affecting both maternal health and child development. The purpose of this study was to determine the prevalence and factors of PPD screened immediately after delivery. Materials and methods: A retrospective study design using secondary data analysis is applied. Four years of data, containing linkable maternal, neonate and PPD screen records between 2014 and 2018, was retrieved and combined from the electronic medical systems of MacKay Memorial Hospital in Taiwan. For each woman, the PPD screen record contained self-reported depressive symptoms assessed by the Edinburgh Postnatal Depression Scale (EPDS) within 48-72 h after delivery. A set of factors pertaining to maternal, pregnancy and obstetric, neonatal and breastfeeding were selected from the combined data set. Results: In total, 10.2% (1244 of 12,198) of women reported with the symptoms of PPD (EPDS ≥10). Through logistic regression analysis, eight predictors of PPD were identified. Specifically, PPD was shown to be associated with educational level of high school or lower (odds ratio (OR) = 1.57, 95% confidence interval (CI) 1.27-1.93), marital status of unmarried (OR = 1.52, 95% CI 1.18-1.99), unemployed (OR = 1.26, 95% CI 1.11-1.42), Cesarean section (OR = 1.7, 95% CI 1.5-1.93), unplanned pregnancy (OR = 1.38, 95% CI = 1.22-1.57), gestational age at 24-36 weeks (OR = 1.3, 95% CI 1.08-1.56), non-intention of breastfeeding (OR = 1.7, 95% CI 1.18-2.45) and Apgar at 5 min < 7 (OR = 2.18, 95% CI 1.11-4.29). Conclusion: Low educational level, unmarried, unemployed, Caesarean section, unplanned pregnancy, preterm delivery, not breastfeeding and low Apgar at 5 min are predictors for postpartum women to develop PPD. These predictors are easily recognized in the clinical environment for patient guidance, support and referral as early as possible to ensure the health and well-being of the mothers and the neonates.